Environmental Governance in Handling Forest and Land Fires in Banjarbaru, South Kalimantan - Muthi’ah Istiqlaliyah; Fitriani; Muthia Afifah Salsabila; Imelda; Iradhad Taqwa Sihidi (Catalist Indo Publisher, 2026)
Background This study aims to analyze the effectiveness of environmental governance in handling forest and land fires (karhutla) in Banjarbaru City, South Kalimantan, during the 2023–2024 period. Forest and land fires in Banjarbaru continue to occur repeatedly despite the local government forming a task force, implementing hotspot monitoring technology, and implementing various mitigation policies. Methods This study uses a descriptive qualitative method with a case study approach. Data were collected through analysis of policy documents, official government reports, hotspot data from relevant agencies, and relevant scientific literature. Data analysis was conducted thematically through the stages of data reduction, presentation, and conclusion drawing. Results The results of the study indicate that environmental governance in handling forest and land fires in Banjarbaru has not been optimal due to institutional fragmentation, weak coordination between actors, limited budget and resource capacity, and low community participation in prevention efforts. In addition, supervision of peatland conversion remains weak, thereby increasing vulnerability to fires. Conclusions This study concludes that strengthening inter-agency coordination, increasing institutional capacity, ensuring transparency of fire information, and adopting a community-based prevention approach are necessary to achieve more effective and sustainable forest and land fire governance.